Composition, method of manufacturing optically anisotropic layer, laminate, polarizing plate, and image display device

JP2025036108APending Publication Date: 2025-03-14FUJIFILM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024098684
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-30
Filing Date
2024-06-19
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、液晶化合物の配向ムラを抑制された光学異方性層を形成できる、組成物を提供することができる。 また、本発明によれば、光学異方性層の製造方法、積層体、偏光板及び画像表示装置を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036108000001
    Figure 2025036108000001
  • Figure 2025036108000002
    Figure 2025036108000002
  • Figure 2025036108000003
    Figure 2025036108000003
Patent Text Reader

Abstract

To provide a composition which enables formation of an optically anisotropic layer with suppressed alignment unevenness of a liquid crystal compound, a method of manufacturing the optically anisotropic layer, a laminate, a polarizing plate, and an image display device.SOLUTION: A composition is provided, comprising a liquid crystal compound, a chiral agent, and a compound represented by one of formulas (1) to (3): M+R1-SO2-N--SO2-R2 ...(1), where M+ represents a lithium cation, sodium cation, or potassium cation, and R1 and R2 independently represent a fluorine atom or an alkyl group substituted with a fluorine atom.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a method for producing an optically anisotropic layer, a laminate, a polarizing plate, and an image display device. [Background technology]

[0002] Optical films (laminates) such as optical compensation sheets and retardation films are used in various image display devices to eliminate image coloration or widen the viewing angle. Stretched birefringent films have been used as optical films, but in recent years, it has been proposed to use optical films having an optically anisotropic layer made of a liquid crystal compound in place of stretched birefringent films.

[0003] As such an optical film, for example, Patent Document 1 describes a laminate including a specific oriented liquid crystal cured film and a substrate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-118729 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have investigated optically anisotropic layers containing ionic compounds including organic cations, as described in Patent Document 1, and have found that there is room for improvement in suppressing uneven alignment of liquid crystal compounds in optically anisotropic layers.

[0006] Therefore, an object of the present invention is to provide a composition capable of forming an optically anisotropic layer in which the alignment unevenness of a liquid crystal compound is suppressed. Another object of the present invention is to provide a method for producing an optically anisotropic layer, a laminate, a polarizing plate and an image display device. [Means for solving the problem]

[0007] As a result of intensive research aimed at achieving the above object, the inventors have found that by using a composition containing a liquid crystal compound, a chiral agent, and a compound represented by formula (1) described below, it is possible to suppress uneven alignment of the liquid crystal compound in an optically anisotropic layer, and have completed the present invention. That is, the present inventors have found that the above problems can be solved by the following configuration.

[0008] [1] A composition comprising a liquid crystal compound, a chiral agent, and a compound represented by any one of formulas (1) to (3) described below. [2] The composition according to [1], wherein the liquid crystal compound is a thermotropic liquid crystal compound. [3] The composition according to [1] or [2], further comprising an organic solvent. [4] The composition according to any one of [1] to [3], wherein the content of the compound represented by any one of the above formulas (1) to (3) is 0.01 to 1.00% by mass with respect to the liquid crystal compound. [5] M + is a lithium cation. [6] A method for producing an optically anisotropic layer, comprising a step of forming an optically anisotropic layer on a substrate using the composition according to any one of [1] to [5]. [7] The substrate includes a support and an alignment film disposed on the support, A method for producing the optically anisotropic layer according to [6], comprising the step of forming an optically anisotropic layer on the alignment film using the composition according to any one of [1] to [5]. [8] The method for producing an optically anisotropic layer according to [6] or [7], wherein the substrate is transported by a grounded metal roll. [9] A laminate comprising a substrate and an optically anisotropic layer disposed on the substrate and formed using the composition according to any one of [1] to [5].

[10] The substrate includes a support and an alignment film disposed on the support, The laminate according to [9], comprising: an optically anisotropic layer disposed on the alignment film and formed using the composition according to any one of [1] to [5].

[11] The laminate according to [9] or

[10] , wherein the optically anisotropic layer includes a region in which the liquid crystal compound is twistedly aligned.

[12] A polarizing plate comprising an optically anisotropic layer formed using the composition according to any one of [1] to [5] above, and a polarizer.

[13] An image display device comprising an optically anisotropic layer formed using the composition according to any one of [1] to [5].

[14] The image display device according to

[13] , which is a liquid crystal display device.

[15] The image display device according to

[13] , which is an organic electroluminescence (EL) display device. Effect of the Invention

[0009] According to the present invention, it is possible to provide a composition capable of forming an optically anisotropic layer in which uneven alignment of a liquid crystal compound is suppressed. Furthermore, according to the present invention, it is possible to provide a method for producing an optically anisotropic layer, a laminate, a polarizing plate, and an image display device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the present specification, each component may be used alone or in combination of two or more substances corresponding to each component. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. In addition, in this specification, "(meth)acrylate" is a notation representing "acrylate" or "methacrylate", and "(meth)acryl" is a notation representing "acryl" or "methacryl". In addition, in the present specification, the bonding direction of a divalent group (e.g., -CO-O-) is not particularly limited unless the bonding position is clearly stated. For example, when L in XLY is -COO-, the bonding position on the X side is *1 and the bonding position on the Y side is *2, then L may be *1-O-CO-*2 or *1-CO-O-*2.

[0011] In the present specification, Re(λ) and Rth(λ) respectively represent the in-plane retardation and the thickness retardation at a wavelength λ, which is 550 nm unless otherwise specified. In the present invention, Re(λ) and Rth(λ) are values ​​measured at a wavelength λ using an AxoScan (manufactured by Axometrics). By inputting the average refractive index ((nx+ny+nz) / 3) and the film thickness (d(μm)) into AxoScan, Slow axis direction (°) Re(λ) = R0(λ) Rth(λ)=((nx+ny) / 2-nz)×d is calculated. Note that R0(λ) is displayed as a numerical value calculated by AxoScan, but it means Re(λ).

[0012] [Composition] The composition of the present invention contains a liquid crystal compound, a chiral agent, and a compound represented by any one of formulas (1) to (3) described below. Hereinafter, the compound represented by formula (1) will be referred to as "compound (1)", the compound represented by formula (2) will be referred to as "compound (2)", and the compound represented by formula (3) will be referred to as "compound (3)". Although the mechanism of action of the present invention is not entirely clear, the present inventors speculate as follows. For example, when an optically anisotropic layer is formed using a composition containing a chiral agent, a method of forming an optically anisotropic layer on a substrate using the composition while conveying the substrate using a roll (particularly a metal roll) can be mentioned. The present inventors have found that when the substrate and / or the optically anisotropic layer obtained in this way is charged and discharge occurs, the magnetic field generated by the discharge tends to cause unevenness in the alignment state of the liquid crystal compound in the optically anisotropic layer. In such a case, it is conceivable to neutralize the charge in the substrate and / or the optically anisotropic layer using a composition containing an ionic compound, but it has been difficult to suppress alignment unevenness even when an ionic compound containing an organic cation is used. On the other hand, it is presumed that compounds (1) to (3) each consisting of an anion having a relatively small size and a strong electron-withdrawing group and a relatively small size cation can sufficiently neutralize the charge, thereby suppressing alignment unevenness. Furthermore, according to the present invention, alignment defects can be suppressed. It has been found that when the above-mentioned ionic compounds are added to a composition containing a liquid crystal compound, the above-mentioned ionic compounds may inhibit the alignment of the liquid crystal compound, resulting in alignment defects in the optically anisotropic layer after coating. Among the above-mentioned ionic compounds, compounds (1) to (3) have a relatively small molecular size, and therefore have a small effect of inhibiting the alignment of the liquid crystal compound, and are considered to be advantageous in terms of suppressing alignment defects.

[0013] The composition is not particularly limited, but is preferably used for forming an optically anisotropic layer, which will be described later.

[0014] The various components that the composition may contain are described in more detail below.

[0015] [Liquid crystal compound] The composition includes a liquid crystal compound. Generally, liquid crystal compounds can be classified into rod-shaped and disk-shaped types based on their shape. Furthermore, each type can be divided into low molecular weight and high molecular weight types. High molecular weight generally refers to a compound with a degree of polymerization of 100 or more (Polymer Physics: Phase Transition Dynamics, Masao Doi, p. 2, Iwanami Shoten, 1992). The liquid crystal compound is not particularly limited, and may be either a rod-shaped or discotic liquid crystal compound. Among them, rod-shaped liquid crystal compounds or discotic liquid crystal compounds (discotic liquid crystal compounds) are preferred, and rod-shaped liquid crystal compounds are more preferred, in terms of the superior effect of the present invention. The liquid crystal compound may be either a thermotropic liquid crystal compound or a lyotropic liquid crystal compound, and is preferably a thermotropic liquid crystal compound.

[0016] The liquid crystal compound is also preferably a liquid crystal compound having a polymerizable group (polymerizable liquid crystal compound). Here, the polymerizable group is not particularly limited, but is preferably a polymerizable group capable of radical polymerization or cationic polymerization. The radically polymerizable group may be any known radically polymerizable group, and an acryloyloxy group or a methacryloyloxy group is preferred. The cationic polymerizable group may be a known cationic polymerizable group, such as an alicyclic ether group, a cyclic acetal group, a cyclic lactone group, a cyclic thioether group, a spiro orthoester group, or a vinyloxy group. Among these, an alicyclic ether group or a vinyloxy group is preferred, and an epoxy group, an oxetanyl group, or a vinyloxy group is more preferred. As the polymerizable group, a polymerizable group represented by any one of formulas (P-1) to (P-20) is also preferred, in which * represents the bonding position.

[0017] [ka]

[0018] As the rod-shaped liquid crystal compound, for example, the rod-shaped liquid crystal compounds described in claim 1 of JP-A-11-513019 and paragraphs

[0026] to

[0098] of JP-A-2005-289980 are preferable. As the discotic liquid crystal compound, for example, the discotic liquid crystal compounds described in paragraphs

[0020] to

[0067] of JP-A-2007-108732 and paragraphs

[0013] to

[0108] of JP-A-2010-244038 are preferable.

[0019] The liquid crystal compound may be a liquid crystal compound with reverse wavelength dispersion. Here, in the present specification, the liquid crystal compound having “reverse wavelength dispersion” refers to a compound in which, when the in-plane retardation (Re) value of a retardation film produced using the compound is measured at a specific wavelength (visible light range), the Re value is equal to or higher as the measured wavelength increases.

[0020] The liquid crystal compound having reverse wavelength dispersion is not particularly limited as long as it can form a film having reverse wavelength dispersion as described above. Examples of the liquid crystal compound having reverse wavelength dispersion include compounds represented by general formula (I) described in JP-A-2008-297210 (particularly, the compounds described in paragraphs

[0034] to

[0039] ), compounds represented by general formula (1) described in JP-A-2010-084032 (particularly, the compounds described in paragraphs

[0067] to

[0073] ), and compounds represented by general formula (1) described in JP-A-2016-081035 (particularly, the compounds described in paragraphs

[0043] to

[0055] ). Further, paragraphs

[0027] to

[0100] of JP 2011-006360 A, paragraphs

[0028] to

[0125] of JP 2011-006361 A, paragraphs

[0034] to

[0298] of JP 2012-207765 A, paragraphs

[0016] to

[0345] of JP 2012-077055 A, paragraphs

[0017] to

[0072] of WO12 / 141245, and paragraphs

[0012] to

[0072] of WO12 / 147904

[0021] to

[0088] , and the compounds described in paragraphs

[0028] to

[0115] of WO14 / 147904.

[0021] The content of the liquid crystal compound is preferably 95% by mass or less, more preferably 1 to 90% by mass, further preferably 1 to 85% by mass, particularly preferably 1 to 80% by mass, based on the total solid content of the composition.

[0022] [Chiral Agents] The composition includes a chiral agent. Chiral agents (optically active compounds) have the function of inducing a helical structure in the cholesteric liquid crystal phase. Chiral agents can be selected according to the purpose, since the twist direction or helical pitch of the helix induced varies depending on the compound. The type of the chiral agent is not particularly limited. The chiral agent may be either liquid crystalline or non-liquid crystalline. Although chiral agents generally contain an asymmetric carbon atom, axially asymmetric or planarly asymmetric compounds that do not contain an asymmetric carbon atom can also be used as chiral agents. Examples of axially asymmetric and planarly asymmetric compounds include binaphthyl, helicene, paracyclophane, and derivatives thereof. The chiral agent may have a polymerizable group. Examples of the polymerizable group include the polymerizable groups that the liquid crystal compound can have. In addition, when two or more types of alignment states are formed in the same layer described later, it is preferable to use two or more types of chiral agents.

[0023] The content of the chiral dopant is preferably from 0.1 to 15% by mass, and more preferably from 0.5 to 10% by mass, based on the total mass of the liquid crystal compound.

[0024] [Compound (1) ~ Compound (3)] The composition contains at least any one of compound (1), compound (2), and compound (3). In other words, the composition contains at least one compound selected from the group consisting of compounds (1) to (3). The composition may contain at least two compounds selected from the above group. For example, the composition may contain both compounds (1) and (2), or may contain all of compounds (1), (2), and (3).

[0025] Compound (1) is a compound represented by formula (1).

[0026] M + R 1 -SO2-N - -SO2-R 2 (1)

[0027] In formula (1), M + represents a lithium cation, a sodium cation, or a potassium cation. R 1 and R 2 each independently represents a fluorine atom or an alkyl group substituted with a fluorine atom.

[0028] M + As the cation, lithium cation or sodium cation is preferable, and lithium cation is more preferable since it has a better effect of suppressing uneven alignment or alignment defects. R 1 and R 2 The alkyl group substituted with a fluorine atom, represented by the following formula (I), may be linear, branched or cyclic. The alkyl group substituted with a fluorine atom preferably has 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, further preferably 1 to 3 carbon atoms, and particularly preferably 1 or 2 carbon atoms. The fluorine atom-substituted alkyl group preferably has 1 to 10 fluorine atoms, more preferably 1 to 5 fluorine atoms, and further preferably 1 to 3 fluorine atoms. As the alkyl group substituted with a fluorine atom, a perfluoroalkyl group is preferable, and a trifluoromethyl group is more preferable, in that the effect of suppressing uneven alignment or alignment defects is more excellent. R 1 and R 2 As the alkyl group, an alkyl group substituted with a fluorine atom is preferable, a perfluoroalkyl group is more preferable, and a trifluoromethyl group is even more preferable, because they have a better effect of suppressing uneven alignment or alignment defects.

[0029] The total number of fluorine atoms contained in the compound (1) is preferably 1-10, and more preferably 2-6.

[0030] Examples of compound (1) include bis(fluorosulfonyl)imidonium salts, (fluorosulfonyl)(trifluoromethanesulfonyl)imidonium salts, and bis(trifluoromethanesulfonyl)imidonium salts. The imidonium salts exemplified above are imido lithium salts, imido sodium salts, or imido potassium salts.

[0031] Compound (2) is a compound represented by formula (2), and compound (3) is a compound represented by formula (3).

[0032] [ka]

[0033] In formula (2), M + represents a lithium cation, a sodium cation, or a potassium cation. L 1 represents a single bond, or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. In formula (3), M + represents a lithium cation, a sodium cation, or a potassium cation. L 2 each independently represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. R 3 and R 4 are each independently a fluorine atom, an alkyl group substituted with a fluorine atom, or *-O(O)CR L * represents the bond position. R L R represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. 3 and R 4 *-O(O)CR L If R L They may be bonded to each other to form a ring.

[0034] M in formula (2) + is M in formula (1). + The same definition and preferred embodiments are also the same.

[0035] L in formula (2) 1 The alkylene group having 1 to 8 carbon atoms and which may be substituted with a fluorine atom, represented by the following formula (I) may be linear, branched or cyclic, and is preferably linear. In the case of an alkylene group having 1 to 8 carbon atoms substituted with a fluorine atom, the alkylene group preferably has 1 to 8 fluorine atoms, more preferably 1 to 5 fluorine atoms, and even more preferably 1 to 3 fluorine atoms. L 1 Examples of the alkylene group represented by the formula (I) include alkylene groups (unsubstituted alkylene groups) such as a methylene group, an ethylene group, a propylene group, a butylene group, and an isopropylene group; and alkylene groups substituted with a fluorine atom, such as a difluoromethylene group, a tetrafluoroethylene group, and a hexafluoropropylene group. L 1 is preferably a single bond or an alkylene group having 1 to 2 carbon atoms, more preferably a single bond or an alkylene group having 1 carbon atom, and further preferably a single bond.

[0036] M in formula (3) + is M in formula (1). + The same definition and preferred embodiments are also the same. L in formula (3) 2 each independently represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. 2 Each group represented by the formula (2) is 1 The same definition and preferred embodiments are also the same.

[0037] R in Equation (3) 3 and R 4 The alkyl group substituted with a fluorine atom represented by the formula (1) is represented by R 1 and R 2 The meaning and preferred embodiments of the alkyl group substituted with a fluorine atom are also the same as those of the alkyl group substituted with a fluorine atom represented by the following formula: R in Equation (3) LThe alkyl group having 1 to 8 carbon atoms which may be substituted with a fluorine atom and which is represented by the following formula (I) may be linear, branched or cyclic, and is preferably linear. In the case where the alkyl group has 1 to 8 carbon atoms and is substituted with a fluorine atom, the alkyl group preferably has 1 to 8 fluorine atoms, more preferably 1 to 5 fluorine atoms, and even more preferably 1 to 3 fluorine atoms. R L Examples of the alkyl group represented by the formula (I) include alkyl groups (unsubstituted alkyl groups) such as a methyl group, an ethyl group, a propyl group, a butyl group, and an isopropyl group; and alkyl groups substituted with a fluorine atom, such as a difluoromethyl group, a tetrafluoroethyl group, and a hexafluoropropyl group. R L is preferably a hydrogen atom or an alkyl group having 1 to 2 carbon atoms, and more preferably a hydrogen atom. R 3 and R 4 As the group, a fluorine atom or *-O(O)CR L is preferred.

[0038] Also, R 3 and R 4 *-O(O)CR L If R L They may be bonded to each other to form a ring. The ring formed above may be either a monocyclic ring or a polycyclic ring, and is preferably a monocyclic ring. The number of ring members in the ring formed is preferably 3 to 12, and more preferably 5 to 7. The ring formed above is R 3 and R 4 *-O(O)CR represented by L In the middle, each R L It is preferable that the ring is formed by bonding together groups formed by removing one hydrogen atom from the group represented by the following formula:

[0039] The compound (3) is preferably a compound represented by formula (3a) or a compound represented by formula (3b).

[0040] [ka]

[0041] In formula (3a), M + represents a lithium cation, a sodium cation, or a potassium cation. L 3 represents a single bond, or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. R 5 and R 6 each independently represents a fluorine atom or an alkyl group substituted with a fluorine atom. In formula (3b), M + represents a lithium cation, a sodium cation, or a potassium cation. L 4 and L 5 each independently represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom.

[0042] M in formula (3a) + is M in formula (1). + The same definition and preferred embodiments are also the same. L in formula (3a) 3 represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. 3 Each group represented by the formula (3) is 2 The same definition and preferred embodiments are also the same.

[0043] R in formula (3a) 5 and R 6 The alkyl group substituted with a fluorine atom represented by the formula (3) is represented by R 3 and R 4 The meaning and preferred embodiments of the alkyl group substituted with a fluorine atom are also the same as those of the alkyl group substituted with a fluorine atom represented by the following formula: R 5 and R 6 is preferably a fluorine atom or a trifluoromethyl group, more preferably a fluorine atom.

[0044] M in formula (3b) + is M in formula (1). + The same definition and preferred embodiments are also the same. L in formula (3b) 4 and L 5 represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. 4 and L 5 Each group represented by the formula (3) is 2 The same definition and preferred embodiments are also the same.

[0045] The content of any one of Compound (1) to Compound (3) is preferably 0.01 to 1.00 mass%, more preferably 0.01 to 0.40 mass%, based on the total mass of the liquid crystal compound. From the viewpoint of being more effective in suppressing alignment unevenness or alignment defects, the content is further preferably 0.04 to 0.20 mass%, and particularly preferably 0.05 to 0.15 mass%. In addition, when the composition contains at least two compounds selected from the group consisting of compound (1), compound (2), and compound (3), the total content of the at least two compounds is preferably within the above range.

[0046] [Polymerization initiator] The composition may include a polymerization initiator. The polymerization initiator is preferably a photopolymerization initiator capable of initiating a polymerization reaction by irradiation with ultraviolet light (for example, light having a wavelength of 10 to 400 nm). Examples of the photopolymerization initiator include α-carbonyl compounds, acyloin ethers, α-hydrocarbon-substituted aromatic acyloin compounds, polynuclear quinone compounds, phenazine compounds, oxadiazole compounds, and compounds having an oxime ester structure.

[0047] When the composition contains a polymerization initiator, the content of the polymerization initiator is preferably from 0.1 to 20% by mass, more preferably from 1 to 8% by mass, based on the total mass of the liquid crystal compound.

[0048] [Organic solvent] The composition preferably comprises an organic solvent. Examples of the organic solvent include organic solvents capable of dissolving each component blended in the composition, and organic solvents having at least one group selected from the group consisting of an ether group, an ester group, a carbonyl group, and an amide group are preferred. Examples of the organic solvent include organic solvents having an ether group, such as diethyl ether, dipropyl ether, diisopropyl ether, tetrahydrofuran, 1,2-dimethoxyethane, and 1,4-dioxane; organic solvents having an ester group, such as ethyl acetate, propyl acetate, butyl acetate, methyl propionate, and ethyl propionate; organic solvents having a carbonyl group, such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, cyclopentanone, and cyclohexanone; and organic solvents having an amide group, such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and hexamethylphosphoric acid triamide.

[0049] When the composition contains an organic solvent, the content of the organic solvent is preferably an amount that makes the solid content concentration of the composition 0.5 to 35 mass %, more preferably an amount that makes 1 to 25 mass %.

[0050] [Surfactant] The composition may also include a surfactant. Surfactants can contribute to the formation of stable or rapid liquid crystal phases, such as nematic and cholesteric phases. Examples of the surfactant include fluorine-containing (meth)acrylate polymers, compounds represented by any one of general formulas (X1) to (X3) described in WO2011 / 162291, compounds represented by general formula (I) described in paragraphs

[0082] to

[0090] of JP2014-119605, and compounds described in paragraphs

[0020] to

[0031] of JP2013-47204. Examples of the fluorine-containing (meth)acrylate polymer include the polymers described in paragraphs

[0018] to

[0043] of JP-A-2007-272185.

[0051] When the composition contains a surfactant, the content of the surfactant is preferably from 0.001 to 10% by mass, and more preferably from 0.05 to 3% by mass, based on the total mass of the liquid crystal compound.

[0052] [Basic Compounds] The composition may contain a basic compound. When the composition contains a basic compound, it is expected to have the effect of making metals used in pipes, tanks, etc. less susceptible to corrosion. The basic compound includes compounds having a nitrogen atom, and may be heterocyclic compounds and their derivatives, as well as amines, anilines and their derivatives. Examples of heterocyclic compounds and derivatives thereof include cyclic amines and derivatives thereof, such as pyridine, piperidine, pyridazine, pyrimidine, pyrazine, pyrrole, imidazole, pyrrolidine, piperazine, morpholine, and tropinone. The basic compound is preferably an aromatic heterocyclic compound having a nitrogen atom. The aromatic heterocyclic compound may have an alkyl group (preferably an alkyl group having 1 to 5 carbon atoms).

[0053] When the composition contains a basic compound, the content of the basic compound is preferably from 0.01 to 10.00% by mass, and more preferably from 0.10 to 3.00% by mass, based on the total mass of the liquid crystal compound.

[0054] [Other Additives] The composition may contain other additives in addition to the above-mentioned components. Examples of other additives include antioxidants, ultraviolet absorbers, sensitizers, stabilizers, plasticizers, chain transfer agents, polymerization inhibitors, defoamers, thickeners, flame retardants, dispersants, and colorants such as dyes and pigments.

[0055] [Laminate] The laminate of the present invention preferably comprises a substrate and an optically anisotropic layer disposed on the substrate (on the surface of the substrate) and formed using a composition, and more preferably the substrate comprises a support and an alignment film disposed on the support, and an optically anisotropic layer disposed on the alignment film and formed using a composition.In other words, the laminate preferably comprises a support, an alignment film, and an optically anisotropic layer in this order. The composition is the composition described above.

[0056] The content of any one of the compounds (1) to (3) in the laminate is preferably 0.01 to 1.00 mass%, more preferably 0.01 to 0.40 mass%, and from the viewpoint of a more excellent effect of suppressing alignment unevenness or alignment defects, is further preferably 0.04 to 0.20 mass%, and particularly preferably 0.05 to 0.15 mass%, based on the total mass of the liquid crystal compound and its cured product. In addition, when the composition contains at least two compounds selected from the group consisting of compound (1), compound (2), and compound (3), the total content of the at least two compounds is preferably within the above range.

[0057] [Base material] The laminate includes a substrate. The substrate is a member for supporting the optically anisotropic layer described below. The substrate preferably has a support and an alignment layer disposed on the support.

[0058] <Support> The type of support is not particularly limited, and any known support can be used. The support is preferably a transparent support, which has a visible light (for example, wavelength 380 to 780 nm) transmittance of 60% or more, preferably 80% or more, and more preferably 90% or more. The support is preferably peelable.

[0059] Examples of the support include a glass substrate and a polymer film. Examples of materials for polymer films include cellulose-based polymers; acrylic-based polymers having acrylic ester polymers such as polymethyl methacrylate and lactone ring-containing polymers; thermoplastic norbornene-based polymers; polycarbonate-based polymers; polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymers; polyolefin-based polymers such as polyethylene, polypropylene and ethylene-propylene copolymers; vinyl chloride-based polymers; amide-based polymers such as nylon and aromatic polyamides; imide-based polymers; sulfone-based polymers; polyethersulfone-based polymers; polyetheretherketone-based polymers; polyphenylene sulfide-based polymers; vinylidene chloride-based polymers; vinyl alcohol-based polymers; vinyl butyral-based polymers; arylate-based polymers; polyoxymethylene-based polymers; epoxy-based polymers; and polymers that are mixtures of these polymers.

[0060] The thickness of the support is preferably from 5 to 60 μm, and more preferably from 5 to 40 μm.

[0061] <Alignment film> The alignment film is preferably disposed on a support (on the surface of the support). The support may also function as an alignment film.

[0062] The alignment film is not particularly limited as long as it has the function of horizontally aligning the liquid crystal compound contained in the composition. Alignment layers are generally made mainly of polymers. Polymer materials for alignment layers are described in many publications and many commercial products are available. The polymer material for the alignment film is preferably polyvinyl alcohol, polyimide or any of their derivatives, and more preferably modified or unmodified polyvinyl alcohol. Examples of the alignment film include the alignment film described in WO2001 / 88574, page 43, line 24 to page 49, line 8; the alignment film made of modified polyvinyl alcohol described in Japanese Patent No. 3907735, paragraphs

[0071] to

[0095] ; and the liquid crystal alignment film formed by the liquid crystal alignment agent described in JP2012-155308A.

[0063] It is also preferable to use a photo-alignment film as the alignment film, since no object comes into contact with the alignment film surface during formation of the alignment film, and deterioration of the surface condition can be prevented. Examples of photo-alignment films include alignment films formed from polymer materials such as polyamide compounds and polyimide compounds described in paragraphs

[0024] to

[0043] of WO2005 / 096041; liquid crystal alignment films formed from a liquid crystal alignment agent having a photo-alignment group described in JP2012-155308A; and LPP-JP265CP, a product name manufactured by Rolic Technologies.

[0064] The thickness of the alignment film is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm, and even more preferably 0.01 to 0.5 μm, from the viewpoint of forming an optically anisotropic layer with a uniform thickness by mitigating surface irregularities that may exist on the support.

[0065] [Optical anisotropic layer] The laminate includes an optically anisotropic layer. The optically anisotropic layer is a layer formed using the above-mentioned composition of the present invention. More specifically, as described in detail in the step of forming an optically anisotropic layer in the method for producing a laminate of the present invention described below, it is preferable that the layer is formed by orienting the liquid crystal compound in a coating film formed by applying a composition and fixing that state, and in this case, it is no longer necessary for the layer to exhibit liquid crystallinity. The optically anisotropic layer is preferably formed on the alignment film (on the surface of the alignment film).

[0066] The thickness of the optically anisotropic layer is preferably from 0.7 to 2.5 μm, and more preferably from 0.9 to 2.2 μm, from the viewpoint of making the device thinner.

[0067] The orientation state of the liquid crystal compound in the optically anisotropic layer may be any of horizontal, vertical, tilted and twisted orientation, and it is preferable that the liquid crystal compound is fixed in a horizontal orientation state relative to the main surface of the optically anisotropic layer. In this specification, the term "horizontal alignment" refers to a state in which the major surface of the optically anisotropic layer is parallel to the long axis direction of the liquid crystal compound. However, this does not require strict parallelism, and in this specification, the term refers to an alignment in which the angle between the major surface of the optically anisotropic layer and the long axis direction of the liquid crystal compound is less than 10°. In the optically anisotropic layer, the angle between the major axis direction of the liquid crystal compound and the main surface of the optically anisotropic layer is preferably from 0 to 5°, more preferably from 0 to 3°, and even more preferably from 0 to 2°.

[0068] The optically anisotropic layer is preferably a positive A plate or a positive C plate, more preferably a positive A plate. In addition, the optically anisotropic layer preferably includes a region having two or more kinds of orientation states in the thickness direction in the same layer, and more preferably includes a region not having a twisted orientation (a region of a positive A plate) and a region having a twisted orientation. The method of forming two or more kinds of orientation states in the same layer will be described later.

[0069] Here, the positive A plate and the positive C plate are defined as follows. When the refractive index in the slow axis direction (the direction in which the in-plane refractive index is maximum) in the film plane is nx, the refractive index in the direction perpendicular to the in-plane slow axis is ny, and the refractive index in the thickness direction is nz, the positive A plate satisfies the relationship in formula (A1), and the positive C plate satisfies the relationship in formula (C1). Note that the positive A plate has a positive Rth value, and the positive C plate has a negative Rth value. Formula (A1) nx>ny≒nz Formula (C1) nz>nx≒ny It should be noted that the above "≒" includes not only the case where the two are completely identical, but also the case where the two are substantially identical. Regarding this "substantially the same," in the case of a positive A plate, for example, when (ny-nz)×d (where d is the thickness of the film) is -10 to 10 nm, preferably -5 to 5 nm, it is also included in "ny≒nz," and when (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, it is also included in "nx≒nz." In addition, in the case of a positive C plate, for example, when (nx-ny)×d (where d is the thickness of the film) is 0 to 10 nm, preferably 0 to 5 nm, it is also included in "nx≒ny."

[0070] When the optically anisotropic layer is a positive A plate, Re(550) is preferably from 100 to 180 nm, more preferably from 120 to 160 nm, further preferably from 130 to 150 nm, and particularly preferably from 130 to 145 nm, in order to function as a λ / 4 plate. Here, the term "λ / 4 plate" refers to a plate having a λ / 4 function, specifically, a plate having the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or circularly polarized light into linearly polarized light).

[0071] [Method of manufacturing optically anisotropic layer] The method for producing an optically anisotropic layer is not particularly limited, but is preferably a method for producing an optically anisotropic layer comprising a step of forming an optically anisotropic layer on a substrate using the above-mentioned composition, and more preferably a method for producing an optically anisotropic layer in which the substrate comprises a support and an alignment film disposed on the support, and the method comprises a step of forming an optically anisotropic layer on the alignment film using the composition.

[0072] One specific example of a procedure for forming an optically anisotropic layer includes applying a composition onto an alignment film contained in a substrate, forming a coating film on the alignment film, aligning the liquid crystal compound in the coating film, and then curing the coating film to form an optically anisotropic layer. Examples of methods for applying the composition onto the alignment film include wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, and die coating. After the composition is applied onto the alignment film, the substrate on which the coating film is formed may be subjected to a drying treatment, if necessary, to remove the solvent.

[0073] The method for orienting the liquid crystal compound in the coating film (orientation treatment) is not particularly limited, and examples thereof include a method of heating the coating film and a method of drying the coating film at room temperature. In the case of a thermotropic liquid crystal compound, the liquid crystal phase formed by the orientation treatment can generally be transitioned by a change in temperature. In the case of a lyotropic liquid crystal compound, the transition can also be achieved by a composition ratio such as the amount of solvent. The conditions for heating the coating are not particularly limited, but the heating temperature is preferably 50 to 150° C., and the heating time is preferably 10 seconds to 5 minutes.

[0074] Next, the coating film in which the liquid crystal compound is oriented is subjected to a curing treatment to form an optically anisotropic layer. The method of the curing treatment is not particularly limited, and examples thereof include light irradiation treatment and heat treatment, with light irradiation treatment being more preferred. The type of light used for exposure is not particularly limited, but ultraviolet light is preferred. The amount of irradiation during exposure is not particularly limited, but is preferably 10 mJ / cm 2 ~50J / cm 2 is preferred, and 20 mJ / cm 2 ~5J / cm 2 In order to promote the polymerization reaction, the reaction may be carried out under heating conditions.

[0075] In the method for producing an optically anisotropic layer, the substrate is preferably transported by a grounded metal roll. In other words, the method for producing an optically anisotropic layer preferably includes a step of forming an optically anisotropic layer on the substrate (preferably on an alignment film) using a composition while transporting the substrate by a grounded metal roll. The metal roll and the grounding method are not particularly limited, and may be any known method.

[0076] In the method for producing an optically anisotropic layer, the following first and second embodiments are preferred in that two or more types of alignment states can be formed in the same optically anisotropic layer. The first embodiment includes the following steps 1 to 5. Step 1: A step of forming a composition layer on a substrate using the above-mentioned composition containing a photosensitive chiral agent whose helical twisting power changes upon irradiation with light as a chiral agent and a liquid crystal compound having a polymerizable group as a liquid crystal compound. Step 2: A step of subjecting the composition layer to a heat treatment to align the liquid crystal compound in the composition layer. Step 3: After step 2, a step of irradiating the composition layer with light under conditions of an oxygen concentration of 1% by volume or more. Step 5: A step of subjecting the composition layer to a heat treatment between step 3 and step 4 described below. Step 4: A step of subjecting the composition layer that has been irradiated with light to a curing treatment to fix the alignment state of the liquid crystal compound and form an optically anisotropic layer having a plurality of regions in which the alignment state of the liquid crystal compound differs along the thickness direction. Although the first embodiment includes step 5, as described below, it may be possible to adopt an embodiment in which step 3 is carried out under heating conditions without carrying out step 5.

[0077] The second embodiment includes the following steps 1 to 4. However, in the second embodiment, step 3 is carried out under heating conditions. Step 1: A step of forming a composition layer on a substrate using the above-mentioned composition containing, as a chiral agent, a photosensitive chiral agent whose helical twisting power changes upon irradiation with light, and, as a liquid crystal compound, a liquid crystal compound having a polymerizable group. Step 2: A step of subjecting the composition layer to a heat treatment to align the liquid crystal compound in the composition layer. Step 3: After step 2, a step of irradiating the composition layer with light under conditions of an oxygen concentration of 1% by volume or more and heating. Step 4: A step of subjecting the composition layer that has been irradiated with light to a curing treatment to fix the alignment state of the liquid crystal compound and form an optically anisotropic layer having a plurality of regions in which the alignment state of the liquid crystal compound differs along the thickness direction. The second embodiment is different from the first embodiment in that step 5 is not performed and step 3 is performed under heating conditions, but the same treatment as in the first embodiment is performed.

[0078] The conditions and preferred embodiments of each treatment in the first and second embodiments can be appropriately selected from the conditions and preferred embodiments of each treatment in the above-mentioned method for producing an optically anisotropic layer and the method for producing a laminate. In addition, the conditions and preferred embodiments of each treatment are preferably the conditions of each treatment in the first and second embodiments of WO2018 / 124198.

[0079] [Method of manufacturing laminate] The laminate can be produced, for example, by a known production method. The method for producing the laminate is preferably a method for producing a laminate that includes the above-mentioned method for producing the optically anisotropic layer.

[0080] [Polarizing plate] The polarizing plate of the present invention includes an optically anisotropic layer and a polarizer. The optically anisotropic layer is a layer formed using the above-mentioned composition, and the preferred embodiments are as described above.

[0081] [Polarizer] The polarizer is not particularly limited as long as it is a member having a function of converting light into a specific linearly polarized light, and is preferably any one of a conventionally known absorptive polarizer and reflective polarizer. Examples of the absorption-type polarizer include an iodine-based polarizer, a dye-based polarizer using a dichroic dye, and a polyene-based polarizer. The iodine-based polarizer and the dye-based polarizer include a coating-type polarizer and a stretching-type polarizer, and a polarizer produced by adsorbing iodine or a dichroic dye to polyvinyl alcohol and stretching the resulting product is preferable. In addition, methods for obtaining a polarizer by stretching and dyeing a laminated film in which a polyvinyl alcohol layer is formed on a substrate are described, for example, in Japanese Patent No. 5048120, Japanese Patent No. 5143918, Japanese Patent No. 4691205, Japanese Patent No. 4751481, and Japanese Patent No. 4751486. ​​These known techniques related to polarizers can also be preferably used. Examples of coating-type polarizers include those described in WO2018 / 124198, WO2018 / 186503, WO2019 / 132020, WO2019 / 132018, WO2019 / 189345, JP2019-197168A, JP2019-194685A, and JP2019-139222A. These known techniques related to polarizers can also be preferably used. Examples of reflective polarizers that can be used include polarizers in which thin films with different birefringence are laminated, wire grid polarizers, and polarizers in which a cholesteric liquid crystal having a selective reflection region is combined with a λ / 4 plate. Among these, a polarizer containing a polyvinyl alcohol resin (a polymer containing -CH2-CHOH- as a repeating unit, in particular at least one selected from the group consisting of polyvinyl alcohol and an ethylene-vinyl alcohol copolymer) is preferred because of its superior adhesion.

[0082] The polarizing plate of the present invention may have, in addition to the above-mentioned members, other optically anisotropic layers, protective films, or other functional layers. Examples of other functional layers include an adhesive layer, a stress relaxation layer, a planarizing layer, an anti-reflection layer, a refractive index adjustment layer, and an ultraviolet absorbing layer.

[0083] When the optically anisotropic layer is a λ / 4 plate (positive A plate), the polarizing plate can be used as a circular polarizing plate. When the polarizing plate is used as a circular polarizing plate, the above-mentioned optically anisotropic layer is a λ / 4 plate (positive A plate), and the angle between the slow axis of the λ / 4 plate and the absorption axis of the polarizer described later is preferably 30 to 60°, more preferably 40 to 50°, even more preferably 42 to 48°, and particularly preferably 45°. Here, the "slow axis" of the λ / 4 plate means the direction in the plane of the λ / 4 plate in which the refractive index is maximum, and the "absorption axis" of the polarizer means the direction in which the absorbance is highest. The polarizing plate can also be used as an optical compensation film for an IPS (In-Plane-Switching) type or FFS (Fringe-Field-Switching) type liquid crystal display device. When the polarizing plate is used as an optical compensation film for an IPS-type or FFS-type liquid crystal display device, it is preferable that the above-mentioned optically anisotropic layer is at least one plate of a laminate of a positive A plate and a positive C plate, and the angle between the slow axis of the positive A plate layer and the absorption axis of the polarizer is perpendicular or parallel, and more specifically, it is more preferable that the angle between the slow axis of the positive A plate layer and the absorption axis of the polarizer is 0 to 5° or 85 to 95°. Furthermore, when the optical compensation film has a polarizer, a positive C plate, and a positive A plate laminated in this order, it is more preferable that the angle between the slow axis of the positive A plate and the absorption axis of the polarizer is parallel. Similarly, when the optical compensation film has a polarizer, a positive A plate, and a positive C plate laminated in this order, it is more preferable that the angle between the slow axis of the positive A plate and the absorption axis of the polarizer is perpendicular. When the polarizing plate of the present invention is used in a liquid crystal display device described later, it is preferable that the angle between the slow axis of the optically anisotropic layer and the absorption axis of the polarizer is parallel or perpendicular. In this specification, "parallel" does not require that they be strictly parallel, but rather means that the angle between one and the other is less than 10°. In addition, in this specification, "orthogonal" does not require that they be strictly perpendicular, but rather means that the angle between one and the other is more than 80° and less than 100°.

[0084] [Protective film] Examples of materials for the protective film include cellulose acylate films (e.g., cellulose triacetate film, cellulose diacetate film, cellulose acetate butyrate film, and cellulose acetate propionate film), polyacrylic resin films such as polymethyl methacrylate, polyolefins such as polyethylene and polypropylene, polyester resin films such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone films, polyurethane resin films, polyester films, polycarbonate films, polysulfone films, polyether films, polymethylpentene films, polyether ketone films, (meth)acrylonitrile films, polyolefins, and polymers having an alicyclic structure (norbornene resins (Arton: product name, manufactured by JSR Corporation, amorphous polyolefins (Zeonex: product name, manufactured by Zeon Corporation))), with cellulose acylate films being preferred.

[0085] The optical properties of the protective film are not particularly limited, but when the protective film is located on the same side as the optically anisotropic layer, it is preferable that the following formula is satisfied. 0nm≦Re(550)≦10nm -40nm≦Rth(550)≦40nm

[0086] [Adhesive Layer] The pressure-sensitive adhesive layer may be disposed between the optically anisotropic layer and the polarizer. The pressure-sensitive adhesive layer may be, for example, a member formed of a substance having a ratio of storage modulus G' to loss modulus G'', measured by a dynamic viscoelasticity measuring device (tan δ=G" / G'), of 0.001 to 1.5. Examples of the substance include pressure-sensitive adhesives and substances that tend to creep. Examples of pressure-sensitive adhesives include polyvinyl alcohol-based pressure-sensitive adhesives.

[0087] [Adhesive layer] The polarizing plate may have an adhesive layer disposed between the optically anisotropic layer and the polarizer. The adhesive layer is preferably a layer formed using a curable adhesive composition that is cured by irradiation with active energy rays or by heating. Examples of the curable adhesive composition include a curable adhesive composition containing a cationically polymerizable compound, and a curable adhesive composition containing a radically polymerizable compound. For the adhesive layer, for example, paragraphs

[0062] to

[0080] of JP 2016-035579 A can be referred to, the contents of which are incorporated herein by reference.

[0088] [Easy adhesive layer] The polarizing plate may have an easy-adhesion layer disposed between the optically anisotropic layer and the polarizer. The adhesive layer has a storage modulus of 1.0×10 at 85° C., which is excellent in adhesion between the optically anisotropic layer and the polarizer and can prevent cracks from occurring in the polarizer. 6 Pa~1.0×10 7 Pa is preferred. Examples of materials for the easy-adhesion layer include polyolefin-based components and polyvinyl alcohol-based components. Examples of the easy-adhesion layer include those described in paragraphs

[0048] to

[0053] of JP2018-036345A.

[0089] [Image display device] The image display device of the present invention is an image display device comprising the optically anisotropic layer of the present invention. The display element used in the image display device is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescence (hereinafter abbreviated as "EL (Electro Luminescence)") display panel, and a plasma display panel. Among these, a liquid crystal cell or an organic EL display panel is preferred, and a liquid crystal cell is more preferred. That is, the image display device is preferably a liquid crystal display device using a liquid crystal cell as a display element, or an organic EL display device using an organic EL display panel as a display element, and more preferably a liquid crystal display device.

[0090] [Liquid crystal display device] A liquid crystal display device, which is an example of an image display device, is a liquid crystal display device that includes the above-mentioned polarizing plate and a liquid crystal cell. Of the polarizing plates provided on both sides of the liquid crystal cell, it is preferable to use the above-mentioned polarizing plate as the front-side polarizing plate, and it is more preferable to use the above-mentioned polarizing plate as the front-side and rear-side polarizing plates. The liquid crystal cell constituting the liquid crystal display device will be described in detail below.

[0091] <Liquid crystal cell> The liquid crystal cell used in the liquid crystal display device is preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, FFS (Fringe-Field-Switching) mode, or TN (Twisted Nematic) mode, but is not limited to these. In a TN mode liquid crystal cell, when no voltage is applied, the rod-shaped liquid crystal molecules are aligned substantially horizontally and further aligned in a twisted manner at an angle of 60 to 120°. TN mode liquid crystal cells are most commonly used as color TFT liquid crystal display devices, and are described in many publications. In a VA mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied. VA mode liquid crystal cells include (1) a narrow-sense VA mode liquid crystal cell (described in JP-A-2-176625) in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and substantially horizontally when voltage is applied, (2) a VA mode multi-domain (MVA mode) liquid crystal cell (described in SID97, Digest of tech. Papers (Proceedings) 28 (1997) 845) in order to expand the viewing angle, (3) a mode (n-ASM mode) liquid crystal cell in which rod-shaped liquid crystal molecules are aligned substantially vertically when no voltage is applied and are aligned in a twisted multi-domain when voltage is applied (described in Proceedings of the Japan Liquid Crystal Discussion Society 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (announced at LCD International 98). The VA mode liquid crystal cell may be any of a PVA (Patterned Vertical Alignment) type, an optical alignment type, and a PSA (Polymer-Sustained Alignment) type. Details of these modes are described in JP-A-2006-215326 and JP-A-2008-538819. In the IPS mode liquid crystal cell, rod-shaped liquid crystal molecules are aligned substantially parallel to the substrate, and the liquid crystal molecules respond in a planar manner when an electric field parallel to the substrate surface is applied. In the IPS mode, the black display is achieved when no electric field is applied, and the absorption axes of the pair of upper and lower polarizing plates are perpendicular to each other. Methods of reducing light leakage during black display in an oblique direction and improving the viewing angle using an optical compensation sheet are disclosed in JP-A-10-054982, JP-A-11-202323, JP-A-9-292522, JP-A-11-133408, JP-A-11-305217, and JP-A-10-307291.

[0092] [Organic EL display device] An example of an organic EL display device, which is an example of an image display device, may have, from the viewing side, a polarizer, a λ / 4 plate (positive A plate) made of the above-mentioned optically anisotropic layer, and an organic EL display panel, in this order. The organic EL display panel is a display panel configured using an organic EL element having an organic light-emitting layer (organic electroluminescence layer) sandwiched between electrodes (a cathode and an anode). The configuration of the organic EL display panel is not particularly limited, and a known configuration may be adopted. EXAMPLES

[0093] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0094] [Example 1] [Preparation of Cellulose Acylate Film (Support)] A cellulose acylate dope having the following composition was placed in a mixing tank, stirred, and further heated at 90° C. for 10 minutes. Thereafter, the obtained composition was filtered through a filter paper having an average pore size of 34 μm and a sintered metal filter having an average pore size of 10 μm to prepare a dope. The solid concentration of the dope was 23.5% by mass, the amount of the plasticizer added was the ratio relative to the cellulose acylate, and the organic solvent of the dope was methylene chloride / methanol / butanol=81 / 18 / 1 (mass ratio).

[0095] ---------------------------------------------------------------------------------- Cellulose Acylate Dope ---------------------------------------------------------------------------------- Cellulose acylate (acetyl substitution degree 2.86, viscosity average polymerization degree 310) 100 parts by mass Sugar ester compound 1 (represented by chemical formula (S4)) 6.0 parts by mass Sugar ester compound 2 (represented by chemical formula (S5)) 2.0 parts by mass Silica particle dispersion (AEROSIL R972, Nippon Aerosil Co., Ltd.) 0.1 part by mass · Organic solvents (methylene chloride / methanol / butanol) ----------------------------------------------------------------------------------

[0096] [ka] JPEG2025036108000005.jpg5583

[0097] The dope prepared above was cast using a drum film-forming machine. Specifically, the dope was cast from a die onto a metal support cooled to 0° C., and then the obtained web (film) was peeled off. The drum was made of SUS. Next, the web (film) obtained by casting was peeled off from the drum, and then dried for 20 minutes in a tenter apparatus in which both ends of the web were clipped and transported at 30 to 40° C. The web was then post-dried by zone heating while being transported by rolls. Next, the obtained web was subjected to knurling and then wound up to prepare a cellulose acylate film.

[0098] <Alkaline saponification treatment> The wound web was passed through a dielectric heating roll at 60°C to raise the film surface temperature to 40°C, and then an alkaline solution with the composition shown below was applied to the band surface of the film using a bar coater at a rate of 14 mL / m. 2 The coating was then conveyed for 10 seconds under a steam-type far-infrared heater manufactured by Noritake Co., Ltd. that had been heated to 110°C. Next, using the same bar coater, pure water was applied at a rate of 3 mL / m 2 Next, the film was washed with water using a fountain coater and then dried with an air knife three times, and then conveyed to a drying zone at 70° C. for 10 seconds to prepare an alkali saponified cellulose acylate film.

[0099] ---------------------------------------------------------------------------------- Alkaline solution ---------------------------------------------------------------------------------- Potassium hydroxide 4.7 parts by weight ·Water 15.8 parts by mass 63.7 parts by weight of isopropanol Surfactant SF-1:C 14 H 29 O(CH2CH2O) 20 H 1.0 parts by mass Propylene glycol 14.8 parts by weight ----------------------------------------------------------------------------------

[0100] [Formation of alignment film] On the surface of the cellulose acylate film that had been subjected to the alkaline saponification treatment, an alignment film composition 1 having the following composition was continuously applied with a wire bar #14. The film was dried with hot air at 60°C for 60 seconds and then with hot air at 100°C for 120 seconds to obtain an alignment film. The alignment film and the cellulose acylate film on the side opposite to the alignment film formation surface were then transported while being in contact with a grounded metal roll.

[0101] ------------------------------------------------------------------ Alignment film composition 1 ------------------------------------------------------------------ 100 parts by weight of the following modified polyvinyl alcohol-1 7.5 parts by weight of the following photopolymerization initiator 1.75 parts by weight of the following hardener 0.75 parts by weight of the following polymer B1 ·Water 2620 parts by mass Methanol 873 parts by weight ------------------------------------------------------------------

[0102] Modified polyvinyl alcohol-1 (In the following formula, the numerical value for each repeating unit indicates the content (mol%) of each repeating unit relative to the total repeating units.)

[0103] [ka]

[0104] Photoinitiator

[0105] [ka]

[0106] Hardener

[0107] [ka]

[0108] Polymer B1

[0109] [ka]

[0110] [Formation of Optically Anisotropic Layer] The alignment film prepared above was subjected to a continuous rubbing treatment. At this time, the longitudinal direction of the long film was parallel to the transport direction, and the angle between the longitudinal direction of the film (transport direction) and the rotation axis of the rubbing roller was 78°. The longitudinal direction of the film (transport direction) was set to 90°, and the clockwise direction was expressed as a positive value with the film width direction as the reference (0°) when observed from the film side, so that the rotation axis of the rubbing roller was at 12°. In other words, the position of the rotation axis of the rubbing roller was rotated 78° counterclockwise with the longitudinal direction of the film as the reference.

[0111] The above-mentioned rubbed cellulose acylate film with an alignment film was used as a substrate, and a composition 1 containing a rod-shaped liquid crystal compound having the following composition was applied to the substrate using a Giesser coater while the substrate was being conveyed with a grounded metal roll to form a composition layer. The absolute value of the weighted average helical twisting power of the chiral agent in the composition layer was 0.0 μm -1 It was. Next, the obtained composition layer was heated at 95° C. for 60 seconds, whereby the rod-like liquid crystal compound in the composition layer was aligned in a predetermined direction. Thereafter, the composition layer was irradiated with ultraviolet light (irradiation dose: 25 mJ / cm ) using a 365 nm LED lamp (manufactured by Acroedge Co., Ltd.) at 30° C. in oxygen-containing air (oxygen concentration: approximately 20% by volume). 2 ). The resulting composition layer was then heated at 95° C. for 10 seconds. Thereafter, nitrogen purging was performed to adjust the oxygen concentration to 100 ppm by volume, and the composition layer was irradiated with ultraviolet light (irradiation dose: 500 mJ / cm) using a metal halide lamp (manufactured by Eye Graphics Co., Ltd.) at 80°C. 2 ), an optically anisotropic layer in which the alignment state of the liquid crystal compound was fixed was formed. In this way, a laminate (F-1) was produced.

[0112] ------------------------------------------------------------------ Composition 1 ------------------------------------------------------------------ 80 parts by weight of the following rod-shaped liquid crystal compound (A) 17 parts by weight of the following rod-shaped liquid crystal compound (B) 3 parts by weight of the following polymerizable compound (C) Ethylene oxide modified trimethylolpropane triacrylate (Viscoat #360, manufactured by Osaka Organic Chemical Co., Ltd.) 4 parts by mass Photopolymerization initiator (Irgacure 819, manufactured by BASF) 3 parts by weight 0.47 parts by mass of the following left-twisted chiral agent (L2) 0.42 parts by weight of the right-twisted chiral agent (R2) 0.08 parts by weight of the following polymer (A) Lithium bis(trifluoromethanesulfonyl)imide (Compound (1), Fujifilm Wako Pure Chemical Industries, Ltd.) 0.10 parts by mass Methyl isobutyl ketone 78 parts by weight Ethyl propionate 78 parts by weight ------------------------------------------------------------------

[0113] Rod-shaped liquid crystal compound (A) [a mixture of the following liquid crystal compounds (RA), (RB), and (RC) in a mass ratio of 84:14:2], a thermotropic liquid crystal compound

[0114] [ka]

[0115] Rod-shaped liquid crystal compound (B), thermotropic liquid crystal compound

[0116] [ka]

[0117] Polymerizable compound (C), thermotropic liquid crystal compound

[0118] [ka]

[0119] Left-twisted chiral agent (L2)

[0120] [ka]

[0121] Right-twisted chiral agent (R2)

[0122] [ka]

[0123] Polymer (A) [Fluorine part: 39% by mass, Mesogen part: 61% by mass]

[0124] [ka]

[0125] The laminate (F-1) prepared above was cut parallel to the rubbing direction, and the optically anisotropic layer was observed from the cross-sectional direction with a polarizing microscope. The optically anisotropic layer had a thickness of 2.7 μm, and the region (second region) of the optically anisotropic layer with a thickness (d2) of 1.3 μm on the substrate side was homogeneously aligned without a twist angle, and the region (first region) of the optically anisotropic layer with a thickness (d1) of 1.4 μm on the air side (opposite side to the substrate) was twistedly aligned. The optical properties of the laminate (F-1) were determined using Axoscan from Axometrics and its analysis software (Multi-Layer Analysis). The product (Δn2d2) of Δn2 and thickness d2 at a wavelength of 550 nm in the second region was 177 nm, the twist angle of the liquid crystal compound was 0°, and the alignment axis angle of the liquid crystal compound relative to the longitudinal direction was -11° on the side in contact with the substrate and -11° on the side in contact with the first region. In addition, the product of Δn1 and thickness d1 (Δn1d1) at a wavelength of 550 nm in the first region was 180 nm, the twist angle of the liquid crystal compound was 80°, and the alignment axis angle of the liquid crystal compound relative to the longitudinal direction was -11° on the side adjacent to the second region and -91° on the air side.

[0126] [Examples 2 to 5, 7 to 11, 13 to 18 and Comparative Examples 1, 4 to 6] A laminate was produced in the same manner as in Example 1, except that the types and amounts of additives were changed as shown in the following Tables 1 and 2. The types and contents of other components other than those shown in Tables 1 and 2 were the same as in Example 1.

[0127] [Example 6] [Formation of Alignment Film Composition] <Monomer mA-1> 4-Aminocyclohexanol (50.0 g), triethylamine (48.3 g), and N,N-dimethylacetamide (800 g) were weighed into a 2 L three-neck flask equipped with a stirring blade, a thermometer, a dropping funnel, and a reflux condenser, and stirred under ice cooling. Next, methacrylic acid chloride (47.5 g) was added dropwise to the flask over 40 minutes using a dropping funnel, and after the dropwise addition was completed, the reaction solution was stirred at 40° C. for 2 hours. After cooling the reaction solution to room temperature (23°C), the reaction solution was suction filtered to remove the precipitated salt. The resulting organic layer was transferred to a 2 L three-neck flask equipped with a stirring blade, a thermometer, a dropping funnel, and a reflux condenser, and stirred under water cooling. Next, N,N-dimethylaminopyridine (10.6 g) and triethylamine (65.9 g) were added to the flask, and 4-n-octyloxycinnamic acid chloride (127.9 g) dissolved in tetrahydrofuran (125 g) was added dropwise to the flask over 30 minutes using a dropping funnel, and after the dropwise addition was completed, the reaction solution was stirred for 6 hours at 50° C. After the reaction solution was cooled to room temperature, it was separated and washed with water, and the obtained organic layer was dried over anhydrous magnesium sulfate, and the obtained solution was concentrated to obtain a yellowish white solid. The obtained yellowish white solid was dissolved in methyl ethyl ketone (400 g) by heating and recrystallized to obtain 76 g of the monomer mA-1 shown below as a white solid (yield 40%).

[0128] [ka]

[0129] <Monomer mB-1> As the monomer mB-1, the following Cyclomer M-100 (manufactured by Daicel Corporation) was used.

[0130] [ka]

[0131] <Synthesis of Polymer P-1> A flask equipped with a cooling tube, a thermometer, and a stirrer was charged with 2-butanone (5 parts by mass) as a solvent, and the flask was refluxed by heating in a water bath while flowing nitrogen into the flask at 5 mL / min. A solution of monomer mA-1 (1.2 parts by mass), monomer mB-1 (8.8 parts by mass), 2,2'-azobis(isobutyronitrile) (1 part by mass) as a polymerization initiator, and 2-butanone (5 parts by mass) as an organic solvent was added dropwise over 3 hours, and the resulting reaction solution was stirred while maintaining the reflux state for another 3 hours. After the reaction was completed, the reaction solution was allowed to cool to room temperature, and 2-butanone (30 parts by mass) was added to the reaction solution to dilute it, thereby obtaining a polymer solution with a polymer concentration of about 20% by mass. The obtained polymer solution was poured into a large excess of methanol to precipitate the polymer, the precipitate was filtered, and the obtained solid was washed with a large amount of methanol, and then dried by blowing air at 50 ° C. for 12 hours to obtain a polymer P-1 having a photoalignment group.

[0132] An alignment film composition 2 was prepared as follows.

[0133] ────────────────────────────────── Alignment film composition 2 ────────────────────────────────── The above polymer P-1 100.00 parts by mass 3.00 parts by weight of the following thermal acid generator D-1 Diisopropylethylamine 0.60 parts by weight Butyl acetate 953.12 parts by weight Methyl ethyl ketone 238.28 parts by mass ──────────────────────────────────

[0134] Thermal acid generator D-1

[0135] [ka]

[0136] The above-mentioned alignment film composition 2 was applied by a bar coater to one side of a cellulose acylate film prepared by the same procedure as in Example 1. The film on which the alignment film composition 2 was applied was then dried on a hot plate at 125°C for 2 minutes to remove the solvent, and a precursor film having a thickness of 0.3 µm was formed. The obtained precursor film was irradiated with polarized ultraviolet light (8 mJ / cm 2 A photo-alignment film was formed on the support by illuminating the support with a light source (using an ultra-high pressure mercury lamp) to obtain a substrate having a photo-alignment film.

[0137] [Formation of Optically Anisotropic Layer] Next, while the obtained substrate was being transported by a grounded metal roll, the following composition 6 was applied onto the photo-alignment film by using a bar coater. The coating film formed on the photo-alignment film was heated to 120°C by hot air, and then cooled to 60°C. After that, the coating film was irradiated with 100 mJ / cm2 at a wavelength of 365 nm by using a high-pressure mercury lamp under a nitrogen atmosphere. 2 The coating was then irradiated with 500 mJ / cm2 of ultraviolet light, followed by heating to 120°C. 2 The coating film was irradiated with ultraviolet light of 1000 nm. By the above-mentioned procedure, the alignment of the liquid crystal compound was fixed, and a laminate of Example 6 including an optically anisotropic layer was produced. The laminate produced above was cut, and the optically anisotropic layer was observed from the cross-sectional direction under a polarizing microscope. The optically anisotropic layer had a thickness of 3.0 μm, and the liquid crystal compound was twisted in the entire layer. The optical properties of the laminate were determined using Axoscan from Axometrics and analysis software (Multi-Layer Analysis) from the same company. At a wavelength of 550 nm, Δnd was 176 nm, and the twist angle of the liquid crystal compound was 87°. When viewed from the liquid crystal layer side, assuming that the width direction of the film is 0° (longitudinal direction is 90°), the in-plane slow axis direction (the alignment axis angle of the liquid crystal compound) was 8° on the air side and 95° on the side in contact with the alignment film.

[0138] ---------------------------------------------------------------------------------- Composition 6 ---------------------------------------------------------------------------------- 39.00 parts by weight of the following polymerizable liquid crystal compound L-1 39.00 parts by weight of the following polymerizable liquid crystal compound L-2 17.00 parts by weight of the following polymerizable liquid crystal compound L-3 ·5.00 parts by mass of the above polymerizable compound (C) 0.50 parts by mass of the following polymerization initiator S-1 (oxime type) 0.60 parts by mass of the left-handed twisted chiral agent (L2) Lithium bis(trifluoromethanesulfonyl)imide (Compound (1), Fujifilm Wako Pure Chemical Industries, Ltd.) 0.10 parts by mass Leveling agent (compound T-1 below) 0.20 parts by weight Cyclopentanone 235.00 parts by mass ----------------------------------------------------------------------------------

[0139] Polymerizable liquid crystal compound L-1, thermotropic liquid crystal compound

[0140] [ka]

[0141] Polymerizable liquid crystal compound L-2, thermotropic liquid crystal compound

[0142] [ka]

[0143] Polymerizable liquid crystal compound L-3, thermotropic liquid crystal compound

[0144] [ka]

[0145] Polymerization initiator S-1

[0146] [ka]

[0147] Compound T-1

[0148] [ka]

[0149] [Example 12] A laminate was produced in the same manner as in Example 1, except that an optically anisotropic layer was formed on the support using Composition 1, without forming an alignment film on the support.

[0150] [Example 19] A laminate was produced in the same manner as in Example 13, except that the types and amounts of additives were changed as shown in Table 2 below, and 0.30 parts by mass of 2,6-lutidine (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to composition 17 to prepare composition 23. The types and contents of other components other than those shown in Table 2 were the same as in Example 13.

[0151] [Comparative Example 2] A laminate was produced in the same manner as in Example 6, except that composition 6 in Example 6 was changed to composition 13.

[0152] ---------------------------------------------------------------------------------- Composition 13 ---------------------------------------------------------------------------------- 39.00 parts by mass of the polymerizable liquid crystal compound L-1 39.00 parts by mass of the polymerizable liquid crystal compound L-2 17.00 parts by mass of the above polymerizable liquid crystal compound L-3 ·5.00 parts by mass of the above polymerizable compound (C) 0.50 parts by mass of the above polymerization initiator S-1 (oxime type) 0.60 parts by mass of the left-handed twisted chiral agent (L2) Leveling agent (compound T-1 above) 0.20 parts by weight Cyclopentanone 235.00 parts by mass ----------------------------------------------------------------------------------

[0153] [Comparative Example 3] A laminate was produced in the same manner as in Example 1, except that the alignment film composition 1 in Example 1 was changed to the alignment film composition 3, and the composition 1 was changed to the composition 12.

[0154] ------------------------------------------------------------------ Alignment film composition 3 ------------------------------------------------------------------ 100 parts by weight of the above modified polyvinyl alcohol-1 7.5 parts by weight of the above photopolymerization initiator 1.75 parts by weight of the above hardener 0.75 parts by weight of the above polymer B1 Lithium bis(trifluoromethanesulfonyl)imide (Compound (1), Fujifilm Wako Pure Chemical Industries, Ltd.) 0.05 parts by mass ·Water 2620 parts by mass Methanol 873 parts by weight ------------------------------------------------------------------

[0155] [evaluation] [Evaluation of Uneven Orientation] An area of ​​1.3 m (width direction) × 1 m (transport direction) in the laminate of each Example and Comparative Example was observed with a light box, and the number of band-like orientation irregularities in the width direction was counted. In practice, A to C are preferable, and A is the most preferable. "A": Not seen at all "B": 1~5 pieces "C": 6~10 pieces "D": 11~20 pieces "E": 21 or more

[0156] [Evaluation of alignment defects] A square film with a side length of 40 mm was cut out from each of the laminates of the Examples and Comparative Examples. The obtained sample was observed at a magnification of 70 mm using a polarizing microscope (10x objective lens) under crossed Nicols. 2 The area of ​​each layer was observed, and the number of orientation defects was evaluated. From a practical standpoint, A to C are preferable, and A is the most preferable. "A": 0~5 pieces "B": 6~20 pieces "C": 21~50 pieces "D": 51 or more

[0157] In the table, "[wt%] to PVA" in the column for compound (1) to compound (3) in the alignment film composition indicates the content (mass%) of any of compounds (1) to (3) relative to the total mass of modified polyvinyl alcohol-1 in the alignment film composition. In the column for compound (1) to compound (3) in the composition, "[wt%] liquid crystal" indicates the content (mass%) of any one of compounds (1) to (3) relative to the total mass of the liquid crystal compounds in the composition. In the column for acrylate monomer in composition, "[wt %] to liquid crystal" indicates the content (mass %) of the acrylate monomer relative to the total mass of the liquid crystal compound in the composition. "Content [wt%] of compound (1) to compound (3) in laminate relative to liquid crystal" indicates the content (mass%) of any of compound (1) to compound (3) relative to the total mass of the liquid crystal compounds and their cured products in the laminate.

[0158] PVA alignment film: An alignment film formed using the above-mentioned modified polyvinyl alcohol-1 Photo-alignment film: the above-mentioned photo-alignment film Li-TFSI: Lithium bis(trifluoromethanesulfonyl)imide (corresponding to formula (1)) ·Na-TFSI: Sodium bis(trifluoromethanesulfonyl)imide (corresponding to formula (1)) K-TFSI: Potassium bis(trifluoromethanesulfonyl)imide (corresponding to formula (1)) Li-FTFSI: Lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide (corresponding to formula (1)) Li-FSI: Lithium bis(fluorosulfonyl)imide (corresponding to formula (1)) K-FSI: Potassium bis(fluorosulfonyl)imide (corresponding to formula (1)) Li-BOB: Lithium bis(oxalato)borate (corresponding to formula (3), manufactured by Tokyo Chemical Industry Co., Ltd.) Li-DFOB: Lithium difluoro(oxalato)borate (corresponding to formula (3), manufactured by Merck Ltd.) ·Na-BOB: Sodium bis(oxalato)borate (corresponding to formula (3), manufactured by Alpha Chemical Co., Ltd.) Li-BX: the following compound (corresponding to formula (2), synthesized with reference to Synthesis Example 1 of Compound (II) in WO 2020 / 022142.)

[0159] [ka]

[0160] [ka]

[0161] [Table 1]

[0162] [Table 2]

[0163] From the results shown in the table, it was confirmed that the optically anisotropic layer formed using the composition of the present invention can suppress uneven alignment of the liquid crystal compound in the optically anisotropic layer. From a comparison of Examples 1 to 5 and 13 to 15, it was confirmed that the effect of suppressing alignment unevenness or alignment defects was superior when the content of any one of compounds (1) to (3) in the composition (when the composition contains at least two compounds selected from the group consisting of compound (1), compound (2) and compound (3), the total content of the at least two compounds) was 0.04 to 0.20 mass % (preferably 0.05 to 0.15 mass %) relative to the liquid crystal compound. From a comparison of Examples 1, 7 to 8, and 17 to 19, M + It has been confirmed that when is a lithium cation, the effect of suppressing uneven alignment or alignment defects is more excellent. From a comparison of Examples 1, 6, and 12, it was confirmed that when the laminate included an alignment film, the effect of suppressing alignment defects was more excellent.

Claims

1. A composition comprising a liquid crystal compound, a chiral agent, and a compound represented by any one of formulas (1) to (3). M + R 1 -SO 2 -N - -SO 2 -R 2 (1) In formula (1), M + represents a lithium cation, a sodium cation, or a potassium cation. R 1 and R 2 each independently represents a fluorine atom or an alkyl group substituted with a fluorine atom. 【Chemistry 1】 In formula (2), M + represents a lithium cation, a sodium cation, or a potassium cation. L 1 represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. In formula (3), M + represents a lithium cation, a sodium cation, or a potassium cation. L 2 each independently represents a single bond or an alkylene group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. R 3 and R 4 each independently represents a fluorine atom, an alkyl group substituted with a fluorine atom, or *-O(O)C-R L * represents the bond position. L R represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms which may be substituted with a fluorine atom. 3 and R 4 *-O(O)C-R L When R represents L They may be bonded to each other to form a ring.

2. The composition of claim 1 , wherein the liquid crystal compound is a thermotropic liquid crystal compound.

3. The composition according to claim 1 or 2, further comprising an organic solvent.

4. 3. The composition according to claim 1, wherein the content of the compound represented by any one of formulas (1) to (3) is 0.01 to 1.00% by mass with respect to the liquid crystal compound.

5. M + The composition of claim 1 or 2, wherein is a lithium cation.

6. A method for producing an optically anisotropic layer, comprising the step of forming an optically anisotropic layer on a substrate using the composition according to claim 1 or 2.

7. The substrate includes a support and an alignment film disposed on the support, A method for producing an optically anisotropic layer according to claim 6, comprising the step of forming an optically anisotropic layer on the alignment film using the composition according to claim 1 or 2.

8. The method for producing an optically anisotropic layer according to claim 6 , wherein the substrate is transported by a grounded metal roll.

9. A laminate comprising a substrate and an optically anisotropic layer disposed on the substrate and formed using the composition according to claim 1 .

10. The substrate includes a support and an alignment film disposed on the support, The laminate according to claim 9, further comprising an optically anisotropic layer formed using the composition according to claim 1 or 2, the optically anisotropic layer being disposed on the alignment film.

11. The laminate according to claim 9 , wherein the optically anisotropic layer comprises a region in which the liquid crystal compound is twistedly aligned.

12. A polarizing plate comprising an optically anisotropic layer formed using the composition according to claim 1 or 2, and a polarizer.

13. An image display device comprising an optically anisotropic layer formed using the composition according to claim 1 or 2.

14. The image display device according to claim 13, which is a liquid crystal display device.

15. The image display device according to claim 13, which is an organic electroluminescence display device.

Citation Information

Patent Citations

  • Laminate, elliptically polarizing plate, and polymerizable liquid crystal composition

    JP2020118729A